Symmetrical Dose-Dependent DNA-Methylation Profiles in Children with Deletion or Duplication of 7q11.23 - Strong, Emma (Am J Hum Genet, 2015)
Epigenetic dysfunction has been implicated in a growing list of disorders that include cancer, neurodevelopmental disorders, and neurodegeneration. Williams syndrome (WS) and 7q11.23 duplication syndrome (Dup7) are rare neurodevelopmental disorders with broad phenotypic spectra caused by deletion and duplication, respectively, of a 1.5-Mb region that includes several genes with a role in epigenetic regulation. We have identified striking differences in DNA methylation across the genome between blood cells from children with WS or Dup7 and blood cells from typically developing (TD) children. Notably, regions that were differentially methylated in both WS and Dup7 displayed a significant and symmetrical gene-dose-dependent effect, such that WS typically showed increased and Dup7 showed decreased DNA methylation. Differentially methylated genes were significantly enriched with genes in pathways involved in neurodevelopment, autism spectrum disorder (ASD) candidate genes, and imprinted genes. Using alignment with ENCODE data, we also found the differentially methylated regions to be enriched with CCCTC-binding factor (CTCF) binding sites. These findings suggest that gene(s) within 7q11.23 alter DNA methylation at specific sites across the genome and result in dose-dependent DNA-methylation profiles in WS and Dup7. Given the extent of DNA-methylation changes and the potential impact on CTCF binding and chromatin regulation, epigenetic mechanisms most likely contribute to the complex neurological phenotypes of WS and Dup7. Our findings highlight the importance of DNA methylation in the pathogenesis of WS and Dup7 and provide molecular mechanisms that are potentially shared by WS, Dup7, and ASD.